Gendered roles drive innovation bundling: a case of mechanized cowpea-living mulch in Ghana - Abdul Rahman, Nurudeen; Ziblila, Rashida Chantima; Sseguya, Haroon; Bekunde, Mateete (International Institute of Tropical Agriculture, 2024)
Maize yields for smallholder farmers in Ghana are low. These farmers operate under a rain-fed cropping system, with declining soil fertility, weed infestation and drought as key challenges.